A SYSTEMATIC REVIEW ON IMPACT OF HUMAN RESOURCES INFORMATION SYSTEM ON HUMAN RESOURCE STRATEGIES: A RESEARCH IN BANKING SECTOR (Journal of Pharmaceutical Negative Results, 2023)
Organizations have to constantly monitor the changes around their internal and external environment in order to compete and maintain the business interests due to the pressure and brutal competitive conditions of technetronic age posed by globalization and Digital Revolution. Human Resources Information System (HRIS) has become an important feature of Human Resource Management (HRM) in the emerging economies including Tanzania. The system has been adopted by several organizations but evaluation of its contribution to organization performance is rarely undertaken. In this paper, we report on the usefulness associated with the Human Resources Information System (HRIS) in banking sector. This study reviews literature and provides a scholarly background to the study by including some contributions given by various researchers as well as different fields were taken into consideration with regards to online mobile adoption. 15 articles from 1996 to 2023 were extracted through systematic procedure of search, also exclusion and inclusion criteria were adopted for the study. Results were found that the HRIS has the potential to enhance the speed and quality of decision making and the realisation of the HR strategy, thereby enhancing organizational effectiveness. After reviewing the literature various benefits of using human resource information system in the banks are found such as data integration, one-time updation, Access to any number of people and accurate data. This paper also provides different suggestions for effective implementation of human resource information system to various managers, employees working in banking sector.